Bee pollen peptides as potent tyrosinase inhibitors with anti-melanogenesis effects in murine b16f10 melanoma cells and zebrafish embryos - Papassara Sangtanoo; Piroonporn Srimongkol; Tanatorn Saisavoey; Songchan Puthong; Anumart Buakeaw; Rutairat Suttisuwan; Marisa Jatupornpipat; Wittaya Pimtong; Onrapak Reamtong; Aphichart Karnchanatat (My University, 2024)
One important functional food ingredient today, valued for its health properties and ability to prevent disease, is bee pollen, which comprises a combination of nectar, pollen from plants, and the secretions of bees. In this research, the tyrosinase (TYR) inhibiting abilities of the peptides derived from bee pollen protein hydrolysates are investigated. Various proteases were utilized to generate these peptides, followed by testing at different concentrations. Tyrosinase inhibition activity was detected in all cases, while the hydrolysate drawn from 5.0% w/v neutrase exhibited the best IC
Keywords: Bee Pollen; Ingredient; Bee Products Chemical Analysis